New York 2140: Utopia in Five Movements. Issue 1 (1st April 2023) - Veselá, Pavla
Abstract : With reference to Kim Stanley Robinson's Pacific Edge (1990), this article analyzes the author's novel New York 2140 (2017). It proposes that, at the outset, utopia appears as an enclave, which is exemplified by the cooperative life in the Met Life tower. Next, a broader approach is assumed towards utopia as counter-hegemony (in the Gramscian sense). The global social transformation in the novel also involves a struggle over past history as well as a recognition of the limitations of the envisioned future history. This last-mentioned narrative aspect in particular is what transforms New York 2140 into a self-reflexive, speculative work of art.